O republicanismo português : (Cultura, história e política) - Catroga, Fernando (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The present article reprises the principle according to which Portuguese Republicanism aimed to be the political expression of a cultural revolution under the aegis of Neo-Enlightenment. However, here, that particular characteristic was taken for granted and it was the point of departure for its own constitutional materialization. In order to achieve this, the forms of selection of a leading and precursor past were emphasized, as well as the new features which drew the distinction towards Monarchy. Therefore, if this demanded the comparative analysis of other republican Constitutions (namely the French Constitution of 1875), it also showed another conditional mark, recurrently underestimated when the parliamentarist nature of the Constitution of 1911 is explained: the phantom of the abuses of the moderator power and of the frequent use of administrative dictatorship experienced under the Constitutional Chart.